Problems of Illegal Logging Cases in Indonesia from The View of Criminal Law - Dadang Sudrajat (IHSA Institute, 2021)
The case of illegal logging or illegal logging which is currently rife in Indonesia, is a crime of forest and environmental destruction, of course the impact generated from these activities is very detrimental to the Indonesian nation. This study uses a descriptive method with a qualitative approach and data triangulation analysis, the results of the study explain that as a country with the 3rd largest forest ownership in the world, Indonesia has a lot of biodiversity and natural resources that are spread to various islands in Indonesia, but behind this phenomenon, turns out to cause a problem caused by a handful of people or corporations who want to destroy forests and the environment to be converted into a place for illegal tree buying and selling transactions, and does not have a valid legal basis, of course this is an action that is very detrimental to many people, because as we know Indonesia's tropical forests have many benefits and functions as a support for the needs of the wider community, for that the government has issued a law to stop and process any person who has changed the function of the forest and caused damage. and losses to the state, then such actions can be categorized as criminal acts, because basically the forest destruction is caused by several factors, and one of them is through the practice of illegal logging or illegal logging of forests and without having an authorized permit from the government.